Middle Aged Smokers and Their Health Problems in Birendranagar Municipality Surkhet - Ban, Mina Kumari (Journal of Gurubaba, 2025)
Smoking is a serious health problem in the modern world. The worldwide tobacco related diseases have caused many deaths. The consumption of tobacco is increasing day by day. Many control measures have been taken to control the use of tobacco but in under developing countries, smoking is increasing day by day due to illiteracy. Smoking is the main cause of diseases like cancer, heart diseases and respiratory infections. So, this study has been carried out to find out the condition of smoking among the middle aged smokers in Birendranagar Municipality of Surkhet district.This study is based on the descriptive research design and is quantitative in nature. It consists of data collected through interview schedule. The respondents were selected by adopting convenience sampling method. The trial test, the interview schedule was administered in Birendranagar Municipality of Surkhet district and the collected data were analyzed, interpreted and tabulated using tables and percentage. After the analysis and interpretation of the data, the finding, conclusion and some recommendations were made. The study comes to the conclusion that 90.66 percent of the Hindu respondents and 2.66 percent of the Muslims suffered from long term physical health problems. The study shows that 37.33 percent of the Dalits and 14 percent of Brahamans had suffered from long term physical health problems among which 50.50 percent were males and females. Most of the respondents were educated up to class five only. The conclusions were drawn from the study improve the health status of the people by encouraging them to quit smoking and realized the standard health status.